Counterfeit Intentions of Pakistani Consumers: Effect of Personal and Social Orientation on Counterfeit Purchasing Intentions - Ammar Hussain (Journal of Management Practices, Humanities and Social Sciences, 2023)
The issues related to counterfeiting and counterfeit purchase intentions have remained a key concern for researchers as well as practitioners in the marketing field. This study aims to assess the purchase intentions of individuals towards counterfeit products by explaining the relationship between the factors: ethical perception, integrity, status consumption, and fashion consciousness. A sample of 334 individuals was surveyed by using a simple random sampling technique, and the data was analyzed using SPSS. The results of the study show that consumers don't consider it unethical to purchase counterfeit products, as most of the respondents have knowingly purchased these products. The status associated with counterfeit products is found to be an important factor. The consumption of counterfeit products is still a new area of research in developing economies. The majority of the previous research has been conducted in developed economies. This study will provide insight into the underlying factors that motivate individuals toward counterfeit intentions